Peningkatan Ketrampilan Siswa Dalam Membuat Web - Asbon Hendra Azhar; Ratih Adinda Destari; Wahyu Sapta Negoro; M. Agung Sutrisno (Jurnal TUNAS, 2023)
The web is a platform that is most often used to create an application. Web-based applications continue to grow rapidly along with the times. Web-based applications have been widely used for various purposes both in the field of sales and biodata. The web can be interpreted as a collection of pages that display various kinds of text information, data, still or moving images, animated data, sound, video or a combination of all of them, both static and dynamic, which form a series of interconnected buildings. related where each is connected by a network of pages or hyperlinks.This website is based on the development of information and communication technology. Through the development of information technology, created a network of interconnected computers. The network known as the internet is continuously converting electronic messages, including e-mail, file transmission, and two-way communication between individuals or computers.